Admission impossible? Self interest and affirmative action - Jimmy Chan; Erik Eyster (The Johns Hopkins University, Department of Economics, 2002)
This paper explains people's preferences for ethnic and racial diversity in higher education through a model based on self interest Although all citizens from the majority group value diversity and their own education in the same way their preferences for the level of diversity as well as the means of achieving it depend on their competitive positions in university admissions High-income majority citizens who tend to have better academic qualifications than lower-income majority candidates prefer more diversity which they want to achieve through affirmative action by displacing marginal majority candidates for marginal minority candidates Lower-income majority candidates prefer less diversity which they want to achieve through admissions rules that partially ignore academic qualifications Data from a CBS/NYT opinion poll confirm these predictions Our model suggests why recently several American universities have replaced race-conscious admissions policies with race-blind policies that de-emphasize standardized tests with little to no effect on diversity Income inequality and competitive admissions both make banning affrmative action more likely.
Keywords: 330; Bildungschancen; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Studium; USA